Engagement civique des électeurs au seuil de l'âge adulte en région parisienne - LaRue Allen; Juliette Berg; Hee Jin Bang (Nantes Université, 2016)
To encourage youth's involvement in civic life, we need to understand the individual and contextual factors that shape their involvement with civic and political issues. This study illustrates how youths' individual characteristics and their interactions with proximal and national contexts relate to their participation in political life. Using survey data collected from 632 students from four ethnically diverse high schools in the Paris region, this paper focuses on data from 245 participants who were of voting age. We examine individual, proximal, and national context factors that may affect youth's involvement using three indices of political and civic engagement: Commitment to Political Activities, Social Movement Participation, and Unconventional Participation. Results showed that youth with greater political knowledge were more likely to engage in Conventional Political Activities. Gender and race/ethnicity also explained some variation in two of the three indices. School and peer contexts were strongly related to each type of engagement, underscoring the importance of citizenship education, collective school efficacy, and open classroom climate for discussion in promoting young adults' political participation.